A comparative study of English and Myanmar syntax in a narrative with a focus on SFPCA elements / Mya Tharaphi Wynn - Wynn, Mya Tharaphi (2012)
This research project examines the similarities and differences between English and Burmese with regard to the functions of SFPCA in clauses. Data for the study come from Swift’s Gulliver’s Travels in simplified English and its Myanmar translation. Analysis of SFPCA elements is based on Bloor and Bloor’s (2004) and Halliday’s (1994) Systemic Functional Grammar theories. Burmese is now officially called Myanmar language which belongs to Burmanic branch of the Tibeto-Burman family, a subfamily of the Sino-Tibetan language family. The English language, on the other hand, belongs to the Indo- European language family. In Myanmar, the kind of grammatical apparatus such as agreement between subject and finite in person, number, or gender, is not as in English. Some of the differences and similarities between these two languages can be traced through their origins. This study compares the positions and functions of SFPCA elements (Subject, Finite, Predicator, Complement, Adjuncts) in both Myanmar and English languages. The findings reveal the differences and similarities between the positions and arrangement of SFPCA in English and Myanmar clauses based on Halliday’s (1994) and Bloor and Bloor’s (2004) Systemic Functional Grammar. The results further show that English and Myanmar languages have some similarities in the positioning of Subject, Adjunct and Complement and at the same time some differences in the arrangement and position of Finite/Predicator. Since this study focuses mainly on SFPCA clause elements, other aspects of grammatical points such as syntax, phonetics, morphology, and semantics are out of the scope of this study. Further studies can be carried out on such aspects to get a better understanding of the meaning and differences of the two languages.